Precarious alliances : cultures of participation in print and other media - Butler, Martin, Dr; Hausmann, Albrecht; Kirchhofer, Anton, 1962- (Cultural and media studies., 2016)
Starting from an analysis of practices of participation in contemporary print and other media, the volume opens up a historical perspective, probing the potential of the concept of participatory cultures for the exploration of past forms of collaboration between individual and collective actors (i.e. authors, editors, publishers, fans, critics etc.). In doing so, the volume sheds new light on the historically, culturally, and medially specific forms and functions as well as on the economic, political and institutional parameters that contributed to the emergence and transformation of what turn out to be precarious alliances.